Where good ideas come from : the natural history of innovation - Johnson, Steven, 1968- (New York : Riverhead Books, 2010)
Johnson addresses an urgent and universal question: What sparks the flash of brilliance? How does groundbreaking innovation happen? He provides the complete, exciting, and encouraging story of how the ideas are born that push careers, lives, society, and culture forward.
With Where Good Ideas Come From, Steven Johnson pairs the insight of his bestselling Everything Bad Is Good for You and the dazzling erudition of The Ghost Map and The Invention of Air to address an urgent and universal question: What sparks the flash of brilliance? How does groundbreaking innovation happen? Answering in his infectious, culturally omnivorous style, using his fluency in fields from neurobiology to popular culture, Johnson provides the complete, exciting, and encouraging story of how we generate the ideas that push our careers, our lives, our society, and our culture forward. Beginning with Charles Darwin's first encounter with the teeming ecosystem of the coral reef and drawing connections to the intellectual hyperproductivity of modern megacities and to the instant success of YouTube, Johnson shows us that the question we need to ask is, What kind of environment fosters the development of good ideas? His answers are never less than revelatory, convincing, and inspiring as Johnson identifies the seven key principles to the genesis of such ideas, and traces them across time and disciplines. Most exhilarating is Johnson's conclusion that with today's tools and environment, radical innovation is extraordinarily accessible to those who know how to cultivate it. Where Good Ideas Come From is essential reading for anyone who wants to know how to come up with tomorrow's great ideas.
Includes bibliographical references (p. [303]-313) and index.
Keywords: Innovatie : ideeën; Creativiteit : innovatie